DIDACTICAL DESIGN RESEARCH AS A STRATEGY FOR DEVELOPING PEDAGOGICAL CONTENT KNOWLEDGE (PCK) IN MATHEMATICS TEACHERS - Tio Heriyana; Hana Astria Nur; Ita Yusritawati; Evan Farhan Wahyu Puadi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
The limited Pedagogical Content Knowledge (PCK) of mathematics teachers is a significant issue that leads to students encountering difficulties in learning about exponentiation and roots. This study seeks to enhance teachers' Pedagogical Content Knowledge (PCK) by implementing the Didactical Design Research (DDR) approach. This qualitative research method was applied to VIII grade students of SMP Negeri 1 Cigugur through a DDR cycle that includes design, implementation, retrospective analysis, and reflection. The results indicated that the reflective cycle of DDR successfully transformed teachers' teaching practices from procedural to more diagnostic and responsive. The main findings are empirical didactical designs that have been revised and tested to overcome students' fundamental learning barriers. It is concluded that DDR is an effective professional development model to empower teachers as learning designers.